The complete shorter fiction - Melville, Herman (David Campbell, 1997)
Tuyển chọn những truyện ngắn Mỹ cùng tác giả thế kỷ 19.: The Piazza Tables, Uncollected stories and sketches, Billy Budd, Sailor.